Analisis Penerapan Metode Activity Based Costing System Dalam Penentuan Harga Pokok Kamar - Aris Subranta (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
This study aims to determine the cost of goods sold calculation of the room, how to calculate the activity based costing method in determining the cost of the room and to determine the magnitude of differences in hospitalization rates using companies and Activity Based Costing in the hotel The Royale Krakatoa. This study used a descriptive method that describes the actual situation existing at The Royale Krakatau, as for the techniques used to collect the data is Research Library (Library Research), field research (field research). It can be concluded, that the results of the calculation of the cost of the room by using the company for this type Standard room Rp 552,466, while for the ABC method for this type of Rp 447 271 standard rooms. From the results obtained can be compared to the difference in the cost of the room that the hotel management has determined Royale Krakatoa with the results of calculations using Activity Based approach Costing.dengan difference Rp. 105 195.